Ciprofloxacin-resistant methicillin-resistant Staphylococcus aureus in an acute-care hospital. - Raviglione, M C (1990)
Use of ciprofloxacin as an alternative to vancomycin for treatment of methicillin-resistant Staphylococcus aureus infection has been paralleled by the emergence of resistant strains. This phenomenon has also been noticed in our hospital. To confirm our observation, methicillin and ciprofloxacin susceptibilities were tested by disk diffusion and broth microdilution techniques. We studied 83 methicillin-resistant Staphylococcus aureus isolates obtained from various sources over a 4-month period. Ciprofloxacin resistance (MIC, greater than 2 micrograms/ml) was detected in 69 isolates (83%). Prior use of ciprofloxacin was reported for 24 of 69 patients with ciprofloxacin-resistant strains and 0 of 14 patients with ciprofloxacin-susceptible strains. The day of detection during the hospital stay and the location of the source patient were not significantly different between resistant and susceptible strains. Bacteriophage typing showed a higher occurrence of nontypeable strains among ciprofloxacin-resistant strains (54%). Review of our microbiology register showed a progressive increase in the rate of resistance to ciprofloxacin during the first year of use, with initial rates being about 10% and recent rates being higher than 80%. On the other hand, methicillin-susceptible S. aureus remained uniformly susceptible to ciprofloxacin (98.4%). We conclude that prior use of ciprofloxacin is an important factor for the selection of ciprofloxacin-resistant strains and that ciprofloxacin has limited usefulness against methicillin-resistant S. aureus.